2018
DOI: 10.1029/2017je005462
|View full text |Cite
|
Sign up to set email alerts
|

The Surface Roughness of Large Craters on Mercury

Abstract: This study investigates how individual large craters on Mercury (diameters of 25–200 km) can produce surface roughness over a range of baselines (the spatial horizontal scale) from 0.5 to 250 km. Surface roughness is a statistical measure of change in surface height over a baseline usually after topography has been detrended. We use root mean square deviation as our measure of surface roughness. Observations of large craters on Mercury at baselines of 0.5–10 km found higher surface roughness values at the cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 34 publications
(111 reference statements)
0
7
0
Order By: Relevance
“…The continuous ejecta deposit is approximately symmetric about the crater and lies within one crater radius of the rim. Surface roughness around this crater has a different pattern with radial distance from those observed around other large, fresh craters on Mercury (Susorney et al, ). This difference is associated with the ropey properties of Hokusai's near‐rim ejecta, and a less pronounced secondary ejecta field, relative to similar‐sized craters Abedin and Stieglitz, which, like Hokusai, lie within the northern smooth plains.…”
Section: Hokusai Observationsmentioning
confidence: 65%
“…The continuous ejecta deposit is approximately symmetric about the crater and lies within one crater radius of the rim. Surface roughness around this crater has a different pattern with radial distance from those observed around other large, fresh craters on Mercury (Susorney et al, ). This difference is associated with the ropey properties of Hokusai's near‐rim ejecta, and a less pronounced secondary ejecta field, relative to similar‐sized craters Abedin and Stieglitz, which, like Hokusai, lie within the northern smooth plains.…”
Section: Hokusai Observationsmentioning
confidence: 65%
“…Large lunar craters are often surrounded by rings of smoother proximal ejecta, while distal ejecta becomes rougher with increasing distance from the crater (Kreslavsky et al, ). Roughness signature of large fresh craters on Mercury is similar to that on the Moon, with some smoother rings in the proximal part of continuous ejecta (Kreslavsky et al, ; Susorney et al, ). Fresh craters are also rough on Mars (Kreslavsky & Head, ), where smooth rings are observed only in a few cases, while typical Martian double‐layer and multilayer continuous ejecta have a high short‐baseline roughness.…”
Section: Discussionmentioning
confidence: 94%
“…Finally, Susorney et al. (2017, 2018) mapped RMS deviation (45–90°N, 0.5–250 km) to study the effects of cratering, volcanism, and tectonism on surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Kreslavsky et al (2014) also demonstrated this comparison by mapping the interquartile range of topographic profile curvature (65-85°N, baselines 0.7-11 km) and used their roughness calculations to suggest regolith on Mercury is thicker than lunar regolith. Finally, Susorney et al (2017Susorney et al ( , 2018 mapped RMS deviation (45-90°N, 0.5-250 km) to study the effects of cratering, volcanism, and tectonism on surface roughness.…”
mentioning
confidence: 99%